A comparative study of hemodynamic changes in dexmedetomidine versus midazolam and fentanyl combination during awake fibreoptic intubation - Baloda, Ritu; Kaur, Jaspreet; Battu, Rupali; Puhal, Sudha (Asian Journal of Medical Sciences, 2021)
Background: The hemodynamic changes during awake fibreoptic intubation (AFOI) are attributed to patient’s anxiety, poor topicalization of the airway, excessive sedation, lack of expertise, pain, prolonged time to intubation, stimulation of oropharyngeal structures, and jaw thrust to aid intubation. In this study, we compared hemodynamic changes of dexmedetomidine (DEX) with midazolam (MDZ) and fentanyl during AFOI. Aims and Objectives: The objective of the study is to compare the hemodynamic changes in DEX alone versus fentanyl- MDZ combination during AFOI. Materials and Methods: Group-I patients (n=30) received DEX 1 μg/kg bolus infusion over 10 min, followed by infusion of 0.1 μg/kg/h titrated to 0.7 μg/kg/h whereas Group-II patients (n=30) received iv fentanyl 2 μg/kg bolus followed by MDZ infusion of 0.02–0.1 mg/kg/h until they were adequately sedated, i.e. Ramsay Sedation Score (RSS) of 3. Hemodynamics including heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), oxygen saturation (SpO2) were recorded when patient is sedated, i.e. at RSS-3, every min of fibrescopy till 5 min and at intubation and every 3rd min post-intubation till 30 min. Results: Measurements of the HRs in the two groups showed significant differences between the two groups at RSS-3, during FOS and post-intubation with the DEX group showing lower mean HRs compared with the MDZ and fentanyl group. SBP and DBP showed a fall in both the groups as compared with the baseline at RSS-3, during FOS and post-intubation; however, no significant differences were noted between the two groups. The mean SpO2values show significant difference between the two groups. (P<0.05) at RSS-3, FOS, post intubation upto 18 min (P<0.05). Conclusion: The use of DEX at 1 mcg/kg bolus slowly over 10 min, with maintenance rates of 0.1–0.7 μg/kg/h, is safe and beneficial for patients undergoing AFOI. Thus, DEX acts like an ideal drug for AFOI. It provides excellent intubating conditions without significant hemodynamic perturbations and risk of hypoxia.